IMPLEMENTATION OF MULTICULTURAL ISLAMIC EDUCATIONAL VALUES AT THE NAVY ACADEMY - Muhammad Syukur; Nur Fajar Arief (Journal Education Multicultural of Islamic Society, 2023)
Education and values of multiculturalism in Islam are an inseparable part of the development of values that live in society. No exception in Islamic religious education (PAI) for members of the naval military, multiculturalism is claimed to contain values that can act as the main glue in realizing integrity in people's lives. This research examines the implementation of multicultural Islamic education values in the Naval Academy (AAL), with a research focus (1) What are the values of multicultural Islamic education developed at the Naval Academy? (2) how is the process of implementing the values of multicultural Islamic education at the Naval Academy? and (3) What is the model for implementing the values of multicultural Islamic education at the Naval Academy? This research was conducted using a qualitative approach with a phenomenological type. The object of this research is devoted to the TK-III cadet education program for the 2016-2017 academic year. Several data collection techniques were used, namely in-depth interviews, participatory observation and documentation. The technique of checking the validity of the data used includes credibility, transferability, dependability, and confirmability. The data analysis of this research uses the Miles and Huberman model with three steps. The results showed three findings as follows. First, conceptually, the Naval Academy takes the view that the concept of brotherhood desired by Islam regarding the plurality of people is a concept of brotherhood or togetherness in multiculturalism. Second, the process of implementing multicultural Islamic values at the Navy Academy refers to the ISD (Instructional System Design) system in its development reflects top-down military-style values. Third, in terms of the implementation model, the Naval Academy implements contextualized learning experiences, with the main focus being on the value of flexibility in addressing multicultural values. These values are then developed into several, such as professionalism, etiquette, humanity, togetherness, honesty, tolerance and respect for differences.